Knowledge, attitudes and strategies on contraceptive utilization among adolescents: views from beneficiaries and parents in City of Kigali - Jean Baptiste Hategekimana; Adolphe Ndikubwimana; Justin Ndayisenga; Fidele Niyitegeka; Daniel Ukwishatse; Serieux Cyubahiro; Bivegete Kenny Ntwali; Absolomon Gashaija; Alice Nyirazigama; Noel Korukire; Felix K. Rubuga; Patrick Karakwende; et al. (Contraception and Reproductive Medicine)
Abstract Introduction Pregnancy among adolescents is a significant public health concern worldwide, particularly in developing countries, including Rwanda. Although contraception could be an effective tool to prevent unintended pregnancy, its utilization among adolescents is often low. Aim This study explored knowledge, attitudes and strategies on contraceptive utilization among adolescents. Methods Mixed method research (MMR) using a cross-sectional design, Sequential explanatory design was used to explore the views from 394 participants in Gitega Sector. This approach was chosen to first quantify the prevalence and patterns of contraceptive use through the questionnaire-based survey, and then to deepen understanding by exploring attitudes, beliefs, and experiences of adolescents and parents through in-depth interviews and focus group discussions. This sequential approach allowed quantitative findings to guide qualitative inquiry, providing richer context to the statistical data. For the quantitative phase, convenience sampling facilitated by the in charge of Health at the sector level and community health workers at the cell level ensured effective access to the study’s target demographic. Qualitative participants were purposively chosen to gain detailed insights from those identified with unique or significant experiences in the initial survey. Data were analyzed using SPSS version 25.0 for quantitative analysis and ATLAS.ti 23 for qualitative analysis. Results The study found that both adolescents and parents (59.1%) have a low level of knowledge about contraceptive utilization, with adolescents (75.5%) showing significantly lower knowledge than parents (46.4%). A majority of the participants, 195 (56.7%), had a positive attitude towards contraceptive utilization among adolescents. Bivariate analysis revealed significant associations between knowledge and socio-demographic factors such as education (P = 0.00) and marital status (P = 0.00), indicating higher knowledge levels among those with higher educational attainment and married individuals. Additionally, attitudes towards contraceptive utilization were significantly influenced by occupation (P = 0.005) and religion (P = 0.00). However, challenges such as the lack of parent-child communication and low knowledge contributed to the low contraceptive usage despite the existing initiatives such as the INGOBYI Activity. Conclusion The findings highlight a need for targeted interventions that address the specific challenges identified, including the lack of knowledge and communication barriers. Improved education and awareness programs for both adolescents and parents, along with supportive community strategies, may enhance contraceptive utilization. A concerted effort involving parents, healthcare providers, and community leaders may foster a supportive environment that encourages responsible and informed contraceptive use among adolescents.